Sovereign wealth funds as a new instrument of climate protection policy? Study of Norway as a pioneer of ethical guidelines for investment policy - Danyel Reiche (Wuppertal Institut für Klima, Umwelt, Energie, 2008)
Norway's abundance of resources is the establishing factor in explaining how the North European state ranks among the countries worldwide with the highest standard of living. Indeed, fossil fuels are finite and after their depletion the Norwegian social welfare state should endure. Therefore, a sovereign wealth fund has been founded in the kingdom in 1990, in which the surpluses from the oil and gas industry sales have been invested from that time on. This method should secure the state's ability to act in the post-petroleum era. At the end of the 1990's the voice of Norwegian society insisted that the sovereign wealth fund should not only be for intergenerational justice, but should also contribute to the implementation of worth and norms of the present country. In the end of 2004 the Parliament (Storting), on the basis of the Graver Report, finally agreed upon ethic regulations for the investment of the sovereign wealth fund. With capital of over 280 billion Euros (figures from 2007), the second largest sovereign wealth fund in the world, they should now only have businesses in their portfolio which adhere to those ethical regulations. In the present paper, the emergence and outcomes of the development of a Third Way between maximising profit and sustainability will be illustrated. The ethical regulations have different dimensions (e.g. no contribution to human rights violations, child labour, serious environmental damages, etc.) to which the present text concentrates on posing the question to what extent sovereign wealth funds could be a new instrument of climate protection policy. For this purpose, the contribution of both main instruments of ethical regulations, Active Ownership and the exclusion of businesses, were analysed as well as the actors which have been created for their implementation. The repercussions reach from dialogs with businesses in the USA to stop lobby activities against Congress-planned climate protection laws, such as an emissions trading system, to adjusting to the exclusion of individual firms from the portfolio of welfare states, due to a breach of ethics. The drawbacks and constraints of a takeover of the Norwegian regulations by other financial actors and its first diffusion effects will be analysed. Finally, this article will deal with the running evaluations of the ethical regulations and Norwegian current and future domestic climate policies. – – Der Ressourcenreichtum Norwegens hat die Grundlage dafür geschaffen, dass der nordeuropäische Staat weltweit zu den Ländern mit dem höchsten Lebensstandard zählt. Doch fossile Energien sind endlich, und auch nach ihrer Erschöpfung soll der norwegische Wohlfahrtstaat Bestand haben. Deshalb wurde in dem Königreich im Jahr 1990 ein Staatsfonds aufgelegt, in dem seither die Überschüsse aus dem Öl- und Gasverkauf angelegt werden. Diese Mittel sollen die Handlungsfähigkeit des Staates in der Post-Petroleum-Ära sicherstellen. Ende der 1990er Jahre wurden in der norwegischen Gesellschaft Stimmen laut, dass der Staatsfonds nicht nur zur intergenerationellen Gerechtigkeit, sondern auch zur Umsetzung der Werte und Normen des Landes in der Gegenwart beitragen solle. Ende 2004 wurden schließlich vom Parlament (Storting) auf Basis des Graver Reports ethische Richtlinien für die Anlagepolitik des Staatsfonds beschlossen. Der mit einem Vermögen von über 280 Mrd. Euro (Stand Ende 2007) zweitgrößte Staatsfonds der Welt soll nun nur noch Unternehmen in seinem Portfolio haben, die diese ethischen Richtlinien einhalten. Im vorliegenden Paper werden Genese und Outcome dieser Entwicklung eines Dritten Weges zwischen Profitmaximierung und Nachhaltigkeit dargestellt. Die Ethik-Richtlinie hat verschiedene Dimensionen (u. a. kein Beitrag zu Menschenrechtsverletzungen, Kinderarbeit, schweren Umweltschäden, etc.), wobei sich der vorliegende Text auf die Fragestellung konzentriert, inwiefern Staatsfonds ein neues Instrument der Klimaschutzpolitik sein können. Dazu werden der Beitrag der beiden Hauptinstrumente der Ethikrichtlinien, das Active Ownership und der Unternehmensausschluss, zum globalen Klimaschutz ebenso analysiert wie die zu ihrer Umsetzung geschaffenen Akteure. Die Bandbreite der Auswirkungen reicht dabei vom Dialog mit Unternehmen in den USA, Lobbytätigkeiten gegen vom Kongress geplante Klimaschutzgesetze einzustellen bis hin zur Verbannung einzelner Firmen aus dem Portfolio des Staatsfonds wegen groben Verstößen gegen die Ethik-Richtlinien. Die Möglichkeiten und Grenzen einer Übernahme der norwegischen Regeln durch andere Akteure der Finanzwirtschaft werden ebenso untersucht wie erste Diffusionseffekte. Schließlich wird auf die laufende Evaluation der Ethik-Richtlinien und auf Stand und Perspektiven norwegischer Klimaschutzinnenpolitik eingegangen.
urn:nbn:de:101:1-2009011300
Keywords: 330